Identification by gene deletion analysis of barS2, a gene involved in the biosynthesis of γ-butyrolactone autoregulator in Streptomyces virginiae - Yong Jik Lee (2018)
Virginiae butanolide (VB) is a member of the γ-butyrolactone autoregulators and triggers the production of streptogramin antibiotics virginiamycin M1and S in Streptomyces virginiae. A VB biosynthetic gene (barS2) was localized in a 10-kb regulatory island which controls the virginiamycin biosynthesis/resistance of S. virginiae, and analyzed by gene disruption/complementation. The barS2 gene is flanked by barS1, another VB biosynthetic gene catalyzing stereospecific reduction of an A-factor-type precursor into a VB-type compound, and barX encoding a pleiotropic regulator for virginiamycin biosynthesis. The deduced product of barS2 possessed moderate similarity to a putative dehydrogenase of Streptomyces venezuelae, encoded by jadW2located in similar gene arrangement to that in the regulatory island of S. virginiae. A barS2-disruptant (strain IC152), created by means of homologous recombination, showed no differences in growth in liquid medium or morphology on solid medium compared to a wild-type strain, suggesting that BarS2 does not play any role in primary metabolism or morphological differentiation of S. virginiae. In contrast, no initiation of virginiamycin production or VB production was detected with the strain IC152 until 18 h of cultivation, at which time full production of virginiamycin occurs in the wild-type strain. The delayed virginiamycin production of the strain IC152 was fully restored to the level of the wild-type strain either by the exogenous addition of VB or by complementation of the intact barS2 gene, indicating that the lack of VB production at the initiation phase of virginiamycin production is the sole reason for the defect of virginiamycin production, and the barS2 gene is of primary importance for VB biosynthesis in S. virginiae. © 2007 Springer-Verlag.